Effects of Instruction Modality and Readback on Accuracy in Following Navigation Commands. - Schneider, Vivian I.; Healy, Alice F.; Barshi, Immanuel (Journal of Experimental Psychology. Applied, 2004)
In 3 experiments, the authors simulated air traffic controllers giving pilots navigation instructions of various lengths. Participants either heard or read the instructions; repeated either all, a reduced form, or none of the instructions; and then followed them by clicking on the specified locations in a space represented by grids on a computer screen. Execution performance for visual presentation was worse than it was for auditory presentation on the longer messages. Repetition of the instructions generally lowered execution performance for longer messages, which required more output, especially with the visual modality, which required phonological recoding from visual input to spoken output. An advantage for reduced over full repetition for visual but not for auditory presentation was attributed to an enhanced visual scanning process. Reprinted by permission of the publisher.